2014
DOI: 10.1038/ajg.2014.235
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Water Exchange vs. Water Immersion During Colonoscope Insertion

Abstract: Water exchange (water infusion with water removal primarily during insertion) and water immersion (water infusion with water removal during withdrawal) reduce patient discomfort during colonoscope insertion compared with air insuffl ation, and represent a major achievement in colonoscopy. Hsieh et al. found that water exchange, relative to water immersion, resulted in more painless insertions to the cecum and improved adenoma detection in the right colon. However, water exchange is also associated with better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…One major drawback for the diffusion of WE has been its long insertion time when compared with the usual gas insufflation colonoscopy, especially considering that the learning curve needs about 100 procedures to achieve sufficient skill, which may hamper its routine implementation. 19,39,40 Our data show that WE cecal intubation time was significantly longer than that of the other techniques (ie, about 3 to 5 minutes), and yet withdrawal time was similar. When evaluating this additional time, it should be considered that in all selected studies, the WE technique was performed by adequately trained and motivated endoscopists; therefore, outside controlled studies, in Figure 1.…”
Section: Discussionmentioning
confidence: 60%
“…One major drawback for the diffusion of WE has been its long insertion time when compared with the usual gas insufflation colonoscopy, especially considering that the learning curve needs about 100 procedures to achieve sufficient skill, which may hamper its routine implementation. 19,39,40 Our data show that WE cecal intubation time was significantly longer than that of the other techniques (ie, about 3 to 5 minutes), and yet withdrawal time was similar. When evaluating this additional time, it should be considered that in all selected studies, the WE technique was performed by adequately trained and motivated endoscopists; therefore, outside controlled studies, in Figure 1.…”
Section: Discussionmentioning
confidence: 60%
“…Although there is no systematic survey to document the uptake of WE colonoscopy in clinical practice, an editorial focused on the procedure time presumed this as a major deterrent to its more widespread use. 9 Subsequent commentaries continued to express concern over the prolonged insertion time, 10 and a recent editorial on the subject 11 provided insight that, at least in the United States, the widespread use of deep sedation during colonoscopy may hinder or delay the wider implementation of WE colonoscopy. Most RCTs included in our study showed comparable insertion and total procedure times between WE and GAS; in those studies that reported a significantly longer insertion time, the mean increase was only 3.9 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] This has a negative impact on room turnaround efficiency and contributed to hampering its wider adoption in clinical practice. [9][10][11] A meta-analysis 7 reported that despite the longest cecal intubation time with WE, it is still comparable with other insertion methods. However, absolute numbers to show the magnitude of the difference were not reported.…”
mentioning
confidence: 99%
“…All of these studies have used 2 different techniques, water exchange (WE) and water immersion (WI). WE, in particular has been shown to increase adenoma detection but it is not clear whether the reason is better mucosal visualization with the water or other attendant features associated with WE 17 . In particular, WE may dramatically change the quality of the bowel preparation, allowing for more adenomas to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The use of water during colonoscopy may improve adenoma detection through several possible mechanisms 17 . It may help to further clear the bowel of any residual stool.…”
Section: Introductionmentioning
confidence: 99%